PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KUALITAS PELAYANAN MELALUI VARIABEL MODERASI LOYALITAS PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIAK - Endrias Moerni Akzani, Nofy; Junaidi, Junaidi; Oemar, Fahmi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This research aims to determine and analyze the influence of employeecompetency on service quality, the influence of organizational commitment onservice quality, the influence of employee competency on service quality throughemployee work loyalty and the influence of organizational commitment on servicequality through employee work loyalty. The data analysis that will be carried outto test this research is using the Partial Least Square (PLS) method. The resultsof this research are that employee competency has a significant effect on thequality of service at the Siak Regency Population and Civil Registration Service.The higher the employee's expertise and motivation, the better the quality of theirservice. In addition, the consequences of the competence possessed byemployees lead to higher job satisfaction, praise received from both society andleadership, and higher rewards or compensation. Organizational commitment hasa significant effect on the quality of service at the Siak Regency Population andCivil Registration Service. If employees have high organizational commitment tothe company, they will be able to improve the quality of services provided.Employee competency has a significant effect on service quality throughemployee work loyalty at the Siak Regency Population and Civil RegistrationService. High employee loyalty in employees comes from the competence theypossess which can create a sense of togetherness which can later have apositive impact on the services provided and maintain the good name of theagency. Organizational commitment has a significant effect on service qualitythrough employee work loyalty at the Siak Regency Population and CivilRegistration Service. Employees have high commitment when carrying out thetask of providing good service and from this high commitment, high loyalty is alsoformed. Keywords : Competence, Organizational Commitment, Service Quality,Employee Loyalty